The crystal structure of N-cyclohexyl-3-hydroxy-4-methoxybenzamide, C14H19NO3 - Zhang Jingxiao; Zhao Xiaoxiao; Cai Chenyu (Zeitschrift für Kristallographie - New Crystal Structures)
C14H19NO3, monoclinic, Cc (no. 9), a = 11.1235(5) Å, b = 15.3724(5) Å, c = 8.1110(3) Å, β = 109.3980(10)°, V = 1308.21(9) Å3, Z = 4, R gt(F) = 0.0300, wR ref(F 2) = 0.0703, T = 170 K.